Abnormal phosphorylation of Tie2/Akt/eNOS signaling pathway and decreased number or function of circulating endothelial progenitor cells in prehypertensive premenopausal women with diabetes mellitus. Issue 1 (December 2016) - Zeng, Haitao; Jiang, Yanping; Tang, Hailin; Ren, Zi; Zeng, Gaofeng; Yang, Zhen
Abstract Backgrounds The number and activity of circulating endothelial progenitor cells (EPCs) in prehypertension is preserved in premenopausal women. However, whether this favorable effect still exists in prehypertensive premenopausal women with diabetes is not clear. Methods This study compared the number and functional activity of circulating EPCs in normotensive or prehypertensive premenopausal women without diabetes mellitus and normotensive or prehypertensive premenopausal women with diabetes mellitus, evaluated the vascular endothelial function in each groups, and investigated the possible underlying mechanism. Results We found that compared with normotensive premenopausal women, the number and function of circulating EPCs, as well as endothelial function evaluated by flow-mediated dilatation (FMD) in prehypertensive premenopausal women were preserved. In parallel, the Tie2/Akt/eNOS signaling pathway and the plasma NO level or NO secretion of circulating EPCs in prehypertensive premenopausal women was also retained. However, in presence of normotension or prehypertension with diabetes mellitus, the number or function of circulating EPCs and FMD in premenopausal women decreased. Similarly, the phosphorylation of Tie2/Akt/eNOS signaling pathway and the plasma NO level or NO secretion of circulating EPCs was reduced in prehypertension premenopausal with diabetes mellitus. Conclusion The present findings firstly demonstrate that the unfavorable effects of diabetes mellitus on number and activity of circulating EPCs in prehypertension premenopausal women, which is at least partially related to the abnormal phosphorylation of Tie2/Akt/eNOS signaling pathway and subsequently reduced nitric oxide bioavailability. The Tie2/Akt/eNOS signaling pathway may be a potential target of vascular protection in prehypertensive premenopausal women with diabetes mellitus.